Towards inclusive food systems: Pandemics, vulnerable groups, and the role of social protection - Kumar, Neha (2021)
Neha Kumar GLOBAL FOOD POLICY REPORT Netherlands Discussion of IFPRI’s 2021 Global Food Policy Report: Transforming Food Systems After COVID-19 Co-Organized by The Dutch Ministry of Foreign Affairs, IFPRI and Netherlands Food Partnership APR 15, 2021 - 08:00 AM TO 09:15 AM EDT